2009
DOI: 10.1007/s00415-009-5198-z
|View full text |Cite
|
Sign up to set email alerts
|

Segawa syndrome due to mutation Q89X in the GCH1 gene: a possible founder effect in Córdoba (southern Spain)

Abstract: Autosomal dominant guanosine triphosphate cyclohydrolase I deficiency is an inborn error of neurotransmitter metabolism, with a prevalence of 0.5 per million, caused by mutations/deletions in the GCH1 gene. The finding of the mutation Q89X in the GCH1 gene in 23 patients from two pedigrees in an area inhabited by a population of 800,000 prompted us to consider that our cohort may have descended from a single founder. Twelve Q89X mutation-positive cases belonging to two families and 100 unrelated control subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 21 publications
0
20
0
1
Order By: Relevance
“…Clinical neurophysiological studies have revealed the heterogeneity of pathophysiologies of this disorder [25]. We consider that the families investigated (family A and family B) belong to the action dystonia type, due to the presentation of some patients of family A during adulthood with focal dystonia and parkinsonism (data not shown) [19], though there was marked variation in the age at onset of symptoms. Furthermore, this was supported because the side predominance of the hypertonus between the sternocleidomastoideus and the muscles of the extremities was ipsilateral in all the cases in which this information was available (patients V-6, V-7, VI-8, and VI-10 of family A; and patients II-2 and III-2 of family B), and the response to levodopa of the action dystonia was sometimes not complete (patient V-6 of family A; and patient III-2 of family B).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Clinical neurophysiological studies have revealed the heterogeneity of pathophysiologies of this disorder [25]. We consider that the families investigated (family A and family B) belong to the action dystonia type, due to the presentation of some patients of family A during adulthood with focal dystonia and parkinsonism (data not shown) [19], though there was marked variation in the age at onset of symptoms. Furthermore, this was supported because the side predominance of the hypertonus between the sternocleidomastoideus and the muscles of the extremities was ipsilateral in all the cases in which this information was available (patients V-6, V-7, VI-8, and VI-10 of family A; and patients II-2 and III-2 of family B), and the response to levodopa of the action dystonia was sometimes not complete (patient V-6 of family A; and patient III-2 of family B).…”
Section: Discussionmentioning
confidence: 98%
“…A large number of GCH1 gene mutation carriers were detected in our community due to a possible founder effect, as described elsewhere [19]. The same mutation in GCH1 causes a wide phenotypic spectrum of clinical variability occurring in this population of affected patients.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…The mechanism of action is likely to be a central antimuscarinic effect [73]. It is frequently used in AADC deficiency and also sometimes in the management of GCH deficiency, especially for those who have experienced l -dopa-related dyskinesia [17, 26, 74, 75]. The side effects are dose related and include drowsiness, confusion, hallucinations, urinary retention, constipation, dry secretions, anorexia, confusion, and psychosis [75].…”
Section: Ancillary Pharmacotherapiesmentioning
confidence: 99%